Micro-agricultural water management technologies for food security in southern Africa: part of the solution or a red herring? - Merrey, Douglas J.; Sally, Hilmy (2008)
This paper is based on a review of experiences with a wide range of micro- agricultural water management technologies in Sub-Saharan Africa with a special emphasis on southern Africa. The major finding of the study is that these technologies have the potential to make major contributions to improving food security, reducing rural poverty and promoting broad-based agricultural growth. However, there are serious policy impediments to successfully scaling out the use of these technologies at both national and regional levels. The paper makes seven specific policy recommendations whose implementation would enable promotion of wider uptake.